Total cerebral small vessel disease score and all-cause mortality in older adults of Amerindian ancestry: The Atahualpa Project. (December 2021) - Del Brutto, Victor J; Mera, Robertino; Recalde, Bettsy Y; Rumbea, Denisse A; Costa, Aldo F; Del Brutto, Oscar H
Introduction: Cerebral small vessel disease (SVD) predicts all-cause mortality in Eastern Asian and Caucasian populations. However, little is known about SVD impact in individuals of different races/ethnic groups. In this study, we sought to estimate the mortality risk according to the total SVD (tSVD) score in older adults of Amerindian ancestry. Methods: Participants aged ≥60 years from the prospective population-based Atahualpa Project cohort underwent brain MRI between June 2012 and June 2017. The tSVD score was calculated based on the presence of moderate-to-severe white matter hyperintensities, enlarged perivascular spaces, one or more lacune, and one or more cerebral microbleed. We ascertained all-cause mortality during post-MRI follow-up. Poisson regression and Cox-proportional hazards models adjusted for demographics and cardiovascular risk were obtained to estimate mortality risk according to the tSVD score. Results: Analysis included 375 participants with available brain MRI and clinical data (mean age 69.0 ± 8.3 years, 56.3% women). The tSVD score was 0 point in 216 individuals (57.6%), 1 point in 71 (18.9%), 2 points in 53 (14.1%), and 3–4 points in 35 (9.3%). Increasing tSVD score was associated with advancing age, hypertension, low level of education, and physical inactivity. Using tSVD score of 0 as reference, a multivariate Poisson regression model showed an increased mortality for individuals with a tSVD score 3–4 points (IRR: 2.27; 95% CI: 1.20–4.28). Likewise, in the Cox-proportional model adjusted for demographics and cardiovascular risk, participants with a tSVD score 3–4 maintained a greater than two-fold mortality risk when compared to those with tSVD score of 0 points (HR: 2.32; 95% CI: 1.23–4.39). Conclusions: High-burden SVD as determined by the tSVD score predicts mortality in community-dwelling older adults of Amerindian ancestry. Incidental diagnosis of covert SVD should prompt aggressive control of cardiovascular health.